PERAN DAN TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH TERKAIT AKTA PEMBERIAN HAK TANGGUNGAN DALAM AKAD MUDHARABAH PADA BANK SYARIAH - Rina Nurhidayati (Universitas Islam Indonesia, 2016)
Abstract This study reviews the concept of binding guarantee of the rights to land in accordance with laws and regulations in Indonesia and Islamic law; as well as the roles and responsibilities associated with APHT PPAT in the contract of Mudharabah Islamic Bank. The method used in this research is normative. The results showed that APHT can not be used on the contract of Mudharabah and Islamic law has its own security institutions, namely Rahn. Roles and responsibilities of PPAT associated with APHT in the contract of Mudharabah Islamic Bank will be explained by Act No. 4 of 1996, Act No. 21 of 2008, Government Regulation No. 37 of 1998, as amended by Regulation No. 24 of 2016, PERKABAN No. 1 of 2006, as amended by PERKABAN No. 23 of 2009 and Theory of Accountability.Keywords: Liability, Land Deed Official, Granting of Warranty Right Deed, Mudharabah Contract and Islamic Bank.